Meningkatkan Hasil Belajar Dalam Mengemukakan Pendapat Dengan Menggunakan Metode Demonstrasi - Jimanto Jimanto (Universitas Mathla'ul Anwar Banten, 2021)
This study aims to improve student learning outcomes on the material to express the opinions of class VII students by using the demonstration method. This type of research is Classroom Action Research (CAR) which is carried out in two cycles in which each cycle has four components, namely planning, action implementation, observation, and reflection. The results showed that the application of the Demonstration method could increase the activity and learning outcomes of expressing the opinions of class VII students. This can be seen from the average percentage of student learning activities in the first cycle of 62.63%, an increase of 24.18% in the second cycle to 86.81%. Similarly, learning outcomes have increased, it can be seen that the average learning outcomes in the first cycle of 76.31% increased by 18.42% in the second cycle to 94.73%.